John - Edwards, M. J. (Mark J.) (Malden, MA : Blackwell Pub., 2004)
"This commentary, which includes a full consideration of the best of modern historical research on the Gospel of John, embraces the full scope of the Gospel, treating themes such as light, life, witness, judgement, and glory. Mark Edwards explores a diverse range of commentaries on, and creative responses to, the Gospel, including early interpretations by Church fathers and Gnostic theologians, medieval mystery plays and pageants, with particular emphasis on the treatment of the Gospel in English poetry. The diverse excerpts from a wide variety of poets enliven the text, suggesting that imaginative response can illuminate the Bible where purely critical analysis has proved unsatisfactory." "The lively style of the volume will appeal to both students and academics. The main issues discussed by contemporary scholars are handled in notes at the beginning and end of each section, and approaches to the Gospel as a whole - from antiquity to the present - are reviewed in the introduction. Through exploration of literature and the arts, this commentary offers an unrivalled account of the social and cultural importance of John's Gospel."--BOOK JACKET.
Includes bibliographical references (p. [211]-228) and index.
Keywords: Bible. -- Commentaries